2018
DOI: 10.1155/2018/2737563
|View full text |Cite
|
Sign up to set email alerts
|

Work Intensity, Low‐Grade Inflammation, and Oxidative Status: A Comparison between Office and Slaughterhouse Workers

Abstract: Limited knowledge exists about the impact of physical workload on oxidative stress in different occupational categories. Thus, we aimed to investigate the oxidative and inflammatory status in employees with different physical workloads. We enrolled a total of 79 male subjects, 27 office workers (mean age 38.8 ± 9.1 years) and 52 heavy workers, in a slaughterhouse (mean age 40.8 ± 8.2 years). Fasting blood was drawn from an antecubital vein in the morning of the midweek before an 8-hour or 12-hour work shift. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
7
13
0
1
Order By: Relevance
“…Increased ROS forms oxidative stress that is followed by an increase in malondialdehyde (MDA), which continues to create imbalance in the body and affect disease progression. 18 19 20 Increased blood glucose can be affected by insulin, which experiences resistance that is influenced by levels of ROS, namely excessive MDA in the cell. Free radicals (MDA) are formed disproportionately by oxidation of nonenzymatic proteins and oxidative degradation of glycated proteins (advanced glycation end products) in type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ROS forms oxidative stress that is followed by an increase in malondialdehyde (MDA), which continues to create imbalance in the body and affect disease progression. 18 19 20 Increased blood glucose can be affected by insulin, which experiences resistance that is influenced by levels of ROS, namely excessive MDA in the cell. Free radicals (MDA) are formed disproportionately by oxidation of nonenzymatic proteins and oxidative degradation of glycated proteins (advanced glycation end products) in type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…It might be assumed that, with adequate nutrition, polyphenols will provide a sufficient level for antioxidative protection, though diabetic and celiac patients could require polyphenol and antioxidant supplementation, perhaps as red grape extracts without sugar and flour. Due to the adaptations in the PPm assay, this method is also suitable for human specimens, as has been shown previously [21] with respect to work intensity between office workers and manual laborers. In a previous clinical pilot study (Lindschinger et al, accepted in MMW; Springer Verlag), we observed an unexpected decrease of the total polpyphenols in serum of the study participants at the end of supplementation (after six weeks) with a vitamin B complex in the range of 2.5 RDA, in spite of a significant increase of each B vitamin.…”
Section: Discussionmentioning
confidence: 93%
“…For the mesaurement of the total antioxidant capacity in respective samples, we used a commercially available colorimetric assay (TAC ® , Labor Diagnostic Nord, Nordhorn, Germany). The method is based on the inhibition of radical mediated coloring of tetramethylbenzidine (TMB) by antioxidants [21,22]. Briefly, 25 µL of standards (Trolox: 0, 0.375, 0.75, 1.5, and 3 mmol) controls and samples were incubated with 100 µL of reagent A, consisting of 30% hydrogenperoxide and citrate-substrate buffer in a proportion of 1:1000 and 50 µL reagent B, consisting of horseradish peroxidase (25 mU), TMB, and a citrate-substrate buffer in a proportion of 1:10:1000, in uncoated microtitre plates.…”
Section: Total Antioxidant Capacitymentioning
confidence: 99%
“…The combined vitamin B supplementation causes a marked decrease in ROS, protein oxidation, and an enhancement of antioxidative enzymes [9,[14][15][16]. Subjects continuously exposed to low-grade oxidative stress, such as manual laborers [17] and patients suffering from schizophrenia [18] or chronic illnesses including cancer, might particularly benefit from the antioxidant and anti-inflammatory impact of the vitamin B in the prevention of lipid peroxidation [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…(Höflein/D., Austria). This method was described previously[17] and is based on the reaction of polyphenols with transition metals that occurs when the Folin-Ciocalteu reagent is used. The dark-coloured complex was measured at 766 nm.…”
mentioning
confidence: 99%